2002
DOI: 10.1203/00006450-200205000-00014
|View full text |Cite
|
Sign up to set email alerts
|

Polyamine Participation in the Maturation of Glycoprotein Fucosylation, but not Sialylation, in Rat Small Intestine

Abstract: The aim of this study was to determine the role of polyamines in the diet-related maturation of the intestinal glycoprotein glycosylation during postnatal development in the rat. The activity of alpha-2,6-sialyltransferase and the sialylated forms of glycoproteins in the intestinal brush-border membranes were found to decrease considerably after weaning, in parallel with the intestinal level of putrescine. By contrast, the activity of alpha-1,2-fucosyltransferases, the mRNA levels for two alpha-1,2-fucosyltran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2004
2004
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 43 publications
0
17
0
Order By: Relevance
“…Moreover, the production of putrescine by this bacterium could be also harmful. The polyamines, including putrescine, play a role in the maturation of the intestine, even when administrated orally [35]. Polyamines administrated orally can act as growth factors with beneficial or detrimental effects, depending on their concentration [36] and there is evidence suggesting that putrescine can cause malignancy in GIT cells [37].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the production of putrescine by this bacterium could be also harmful. The polyamines, including putrescine, play a role in the maturation of the intestine, even when administrated orally [35]. Polyamines administrated orally can act as growth factors with beneficial or detrimental effects, depending on their concentration [36] and there is evidence suggesting that putrescine can cause malignancy in GIT cells [37].…”
Section: Resultsmentioning
confidence: 99%
“…The mucosa of neonatal piglets itself could have used them for its own metabolism, since polyamine absorption by the gut was reported to be very fast and complet. (30,31) Nevertheless, Delzenne et al (14) reported that in adult rats, fed diets containing oligofructose (10%) for 4 weeks, the concentration of putrescine in the cecal content had almost doubled and increased polyamine concentration in cecal tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Polyamines are produced by bacteria and found in food, and their concentration in the gut increases at weaning concurrent with the increase in fucosylation. Feeding polyamines to young rats results in early development of fucosylation (22). Gavage of the cAMP-activating toxin from a pathogen, Vibrio cholerae, is also effective (3).…”
Section: Developmental and Environmental Control Of Fucosylation In Tmentioning
confidence: 99%